Investigating the bottom free surface nappe (Ogee profile) across a sharp-crested weir influenced by the flow in an asymmetrical approach channel - Van Vuuren, S.J. (University of Pretoria, 2014)
Dissertation (MEng)--University of Pretoria, 2013.